The VARIATION OF THE AXIAL LOCATION OF BRUCH’S MEMBRANE OPENING, GANGLION CELL INNER PLEXIFORM LAYER AND FLUX INDEX IN NORMAL TENSION GLAUCOMA AND PRIMARY OPEN ANGLE GLAUCOMA PATIENTS - Jehan Fauzi Jehan; Retno Ekantini; Tatang Talka Gani; Krisna Dwi Purnomo Jati (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction. Bruch’s membrane opening (BMO) at the most anterior point of the neural canal for quantification of cup depth /based on retinal surface position, area and volume, laminar position, and prelaminar connective tissue volume. If these deep structural parameters are to be used effectively in glaucoma detection and identification of progression. Purpose. This study explores variation in the axial location of Bruch’s membrane opening (BMO) to determine if this reference plane varies with NTG and POAG patients. Methods This was a cross-sectional prospective descriptive study with purposive sampling. This study enrolled 72 eyes in Sardjito General Hospital underwent cirrus – OCT 5000 Ver 11.0.0.29946 between 1st March 2022 and 10th May 2022. Results. We evaluated 72 (25 NTG and 47 POAG) eyes on 37 outpatients service of Sardjito General Hospital. Median BMO, GCIPL, Flux index and CD ratio of NTG patients was 1.707 µm (1.387-2.182), 83,0µm (76-88), 0,40 (0.27-0,48), 0,64 (0,22-0,75). Median BMO, GCIPL, Flux index and CD ratio of POAG patients was 1.612 (1.028-2.031) µm, 79,00 (56-98) µm, 0,40 (0,26-0,47) and 0,64 (0,28-0,92) for CDR. Bruch’s membrane opening position was more posterior relative to the sclera in older subjects with negative correlation (P value = 0,07). Variable BMO and GCIPL tested between NTG and POAG group showed significant difference with BMO P value =0,04 and GCIPL P value=0,01 except Perfusion, flux index and RNFL. Conclusion. Bruch’s membrane opening is more posteriorly located in older individuals. There was significant difference p value of BMO between the mean of NTG and POAG.